Effectiveness and safety of serplulimab plus platinum-based chemotherapy in first-line treatment of extensive-stage small cell lung cancer liver metastases: a retrospective cohort study - Chen, Yifei; Su, Wenzhong (Frontiers in Oncology, 2025)
BackgroundThe role of immunotherapy in patients with extensive-stage small cell lung cancer (ES-SCLC) liver metastases remains controversial. This study aimed to evaluate the effectiveness and safety of serplulimab combined with platinum-based chemotherapy as a first-line treatment for these patients.MethodsThis retrospective cohort study reviewed patients with ES-SCLC liver metastases who received serplulimab plus platinum-based chemotherapy as a first-line treatment. Outcomes included objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and safety. The associations between prognosis and the depth of remission of primary lung lesions and liver metastases were analyzed.ResultsAmong the 30 ES-SCLC patients (median age, 67 years), the ORR was 63.3% (95% CI, 43.9-80.1), and the DCR was 83.3% (95% CI, 65.3-94.4). The median PFS was 5.9 months (95% CI, 4.3-8.1), and the median OS was 9.1 months (95% CI, 6.1-16.2). Patients with a depth of remission of primary lung lesions ≥30% (n=14) had a significantly longer median PFS (8.1 months [95% CI, 6.4-NE] vs. 3.9 months [95% CI, 3.2-6.3], HR:0.28, 95%CI: 0.12-0.65) and OS (16.2 months [95% CI, 9.1-NE] vs. 5.5 months [95% CI, 3.7-13.6], HR: 0.31, 95%CI: 0.12-0.81) than those with a depth of remission <30% (n=16). Patients with a depth of remission of liver metastases ≥30% (n=9) had a significantly extended median OS than those with a depth of remission <30% (n=20) (16.2 months [95% CI, 10.4-NE] vs. 6.3 months [95% CI, 4.4-13.6], HR: 0.21, 95%CI: 0.06-0.73). The most common adverse events were nausea (40.0%), leukopenia (26.7%), and neutropenia (26.7%).ConclusionThis real-world study demonstrates promising effectiveness and a manageable safety profile for the combination of serplulimab with platinum-based chemotherapy in treating ES-SCLC liver metastases, which suggests that this treatment regimen may provide an attractive option for the first-line management of ES-SCLC liver metastases.